Studi Analisis Dampak Pemasangan Over Load Shedding Terhadap Pembebanan Pada Saluran Transmisi 150KV di Bali - Pradnya, Made Ananta; Arjana, I G Dyana; Wijaya, I Wayan Arta (Majalah Ilmiah Teknologi Elektro, 2016)
Safety system supply of electrical power to the transmission system is very important, to maintain the continuity of the load flow of electrical power. PT PLN (Persero) has continued to develop a security system, one with Over Load Shedding or OLS. Over Load Shedding is a form of action over load shedding that occurs automatically or manually installed on the transmission line as security in order to avoid or prevent the occurrence of total outages. This thesis is a case study occurred Cable Channels Over Load on Sea in Bali (January 2015), which reached 432MW from 340MW capacity may be burdened besides GI Gilimanuk and GI Pesanggaran Trip 125.4MW so OLS stage 1 and stage 2 works by removing loads of 89.76MW. Load flow analysis results simulated using ETAP software Powerstation when OLS stage 1 work, the load flow into 359.532MW Submarine Cable Channels and when OLS stage 2 work, the load flow Submarine Cable Channels be 339.664MW, OLS worked for 9 seconds until the flow of electrical power loss can kontiyuitas met and the loadflow on the 150 kV transmission system in Bali is maintained.
Keywords: Analisa Aliran daya (Load Flow Analisys); OLS (Over Load Shedding); ETAP Powerstation